DYSGERMINOMA REGIONAL DE AREQUIPA HONORIO DELGADO HOSPITAL. (July 1960 - July 1986) - Cornejo Gutiérrez Ballón, Carlos (2015)
Between 1960 and 1986. Dysgerminomas tumors are relatively rare, are about 1% of ovarian neoplasms - a study of nine cases of dysgerminoma registered in the Department of Gynecology, Regional Hospital Honorio Delgado (Peru Arequipa) is performed. In our series it constituted 0.32% of primary ovarian tumors, and 13.24% of malignant. A higher incidence between the second and third decade of life demonstrates. No significant change was found with menarche; the catamenial regime retained its regularity. The presence of tumor and abdominal pain are constant facts and should direct to the presumption diagnosis of this disease. There was an association with pregnancy in two patients. In most cases, surgical treatment was conservative. Clinical pathological findings in the context of similar publications is discussed and deducting it difficult to pinpoint the diagnosis because the clinical manifestations of dysgerminomas are usually similar to those produced by other pelvic-abdominal tumors.